HIF-1α enhances autophagy to alleviate apoptosis in marginal cells in the stria vascular in neonatal rats under hypoxia. (August 2022) - Huang, Sihan; Zhao, Yanyun; Liu, Jun
Abstract: In the cochlea, various factors, such as noise, aging, and inflammation, induce hypoxia, resulting in the up-regulation of hypoxia inducible factor-1α (HIF-1α). The role of HIF-1α in hypoxic marginal cells (MCs) of the stria vascularis is unknown. This study examined HIF-1α-mediated autophagy in MCs of neonatal rats and its mechanism of action. We found that an increase in HIF-1α expression was associated with autophagy and apoptosis. Treatment with PX478, a specific inhibitor of HIF-1α, decreased the HIF-1α level, and the degree of autophagy decreased in hypoxic and apoptotic MCs. By contrast, treatment with DMOG, an activator of HIF-1α, increased autophagy and decreased apoptosis. Both PX478 and DMOG had no effect on the apoptotic rate after treatment with 3-methyladenine, an inhibitor of autophagy, indicating that HIF-1α promoted autophagy to protect MCs from hypoxia-induced apoptosis. Lastly, we silenced Bnip3(Bcl-2/adenovirus E1B 19-kDa interacting protein) in MCs to identify the mechanism of action. Our results show that the HIF-1α–BNIP3 pathway mediates the anti-apoptotic effects through an increase in autophagy.